(untitled) (Journal of responsible AI & ethics, 2026)
Artificial intelligence systems are increasingly integrated into modern decision-making environments such as healthcare, finance, education, governance, and digital commerce. As algorithmic systems become more influential in shaping societal outcomes, concerns regarding algorithmic bias, accountability, transparency, and ethical governance have intensified. Algorithmic transparency refers to the ability to understand how automated decision systems operate, including the logic, training data, model structure, and reasoning processes used to generate outputs. Transparent systems are essential for building public trust, ethical compliance, and responsible technological innovation. This paper explores the importance of algorithmic transparency as a foundational element of ethical artificial intelligence systems. The research investigates the relationship between transparency mechanisms, ethical AI governance, and public trust in automated systems. Through a combination of conceptual analysis, empirical observations, and case studies of algorithmic decision systems, the study evaluates how transparency contributes to fairness, accountability, and responsible AI deployment.